Exercise and chemotherapy-induced amenorrhea. (July 2018) - Mathis, Katlynn M.; Sturgeon, Kathleen M.; Winkels, Renate M.; Wiskemann, Joachim; Williams, Nancy I.; Schmitz, Kathryn
Abstract: Chemotherapy-induced amenorrhea (CIA) is the temporary or permanent loss of menses experienced by premenopausal women undergoing chemotherapy treatment for cancer. Two possible mechanisms through which chemotherapy induces CIA have been identified: systemic endothelial dysfunction, resulting in decreased blood flow to the ovaries, and increased oxidative stress within the ovaries, both of which are proposed to lead to apoptosis of follicles. Endothelial dysfunction in ovarian arteries in women undergoing or who have undergone chemotherapy treatment is characterized by prothrombotic changes and thickening of the vascular wall. These changes result in occlusion of the blood vessels. Oxidative stress is increased and antioxidants decreased in the ovaries secondary to chemotherapy drugs, specifically cyclophosphamide. It is hypothesized that low to moderate intensity aerobic exercise during chemotherapy may prevent these changes and lessen the risk for developing CIA in premenopausal women. Low to moderate intensity aerobic exercise has been shown to improve endothelial function and blood flow in patients with cardiovascular disease—a disease state characterized by endothelial dysfunction and for which patients who have undergone chemotherapy are at increased risk. In mice, moderate intensity aerobic exercise has been shown to decrease the amount of oxidative stress within the ovaries, and in humans, chronic aerobic exercise has been shown to increase antioxidant production systemically. This hypothesis should be tested in both a mouse model, using sedentary and exercising mice treated with chemotherapy drugs that commonly result in CIA, as well as a human model to determine the effects of low to moderate intensity aerobic exercise on ovarian function in premenopausal women undergoing chemotherapy.